Pigment Production of Monascus sp. Isolated from Angkak in Semarang Region, Central Java, Indonesia - Endang Kusdiyantini; Soni Nugraha; Arina Lunggani (Indonesian Association of Food Technologists, 2017)
Angkak (red fungi rice, red yeast rice) is a traditional fermentation by fungi Monascus in a lot of Asia Countries, which is useful as a natural food colorant. The aim of this research was to obtain pure isolate of red fungus from angkak in Semarang. The growth and the red pigment production of the selected isolate in the different initial medium pH and nitrogen sources were observed. The treatment was done by growing the isolate in PDB (Potato Dextrose Broth) medium at initial pH 3, 5, 7 and 9 and as well as optimization of nitrogen sources with 1% ammonium chloride, 1% ammonium nitrate, and 1% peptone. Analysis of the fungi growth was performed by weighing mycelia biomass using dry weight method and the red pigments were analysis using spectrophotometer at a wavelength (λmax) of 500 nm. The results showed that the highest absorbance value of pigment (0.81) was obtained at pH 7, and the highest value of the cell dry weight was also obtained at pH 7 (1.23 g/L). The results showed that 1% ammonium chloride was the best nitrogen source for absorbance of red pigment production (0.82), but the highest of dry weight (2.56 g/L) was obtained by using medium with 1% ammonium nitrate as a nitrogen source.